2012
DOI: 10.1002/prca.201100068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a membrane‐enriched proteome from postmortem human brain tissue in Alzheimer's disease

Abstract: Purpose The present study is a discovery mode proteomics analysis of the membrane enriched fraction of post-mortem brain tissue from Alzheimer’s disease (AD) and control cases. This study aims to validate a method to identify new proteins that could be involved in the pathogenesis of AD and potentially serve as disease biomarkers. Experimental Design Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to analyze the membrane enriched fraction of human post-mortem brain tissue from five AD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 56 publications
3
72
0
Order By: Relevance
“…In a previous study, CKBB and respiratory chain complexes activities were both observed to be altered by monoamine-based antidepressants in rat brain (Réus et al, 2012). Moreover, overexpression of CKBB has been demonstrated to be associated with AD (Donovan et al, 2012). Our proteomic data and the results of previous studies suggest that BT may disturb energy homeostasis in the CNS of fish, potentially leading to neurodegeneration; however this hypothesis must be tested in additional experiments.…”
Section: Discussionsupporting
confidence: 46%
“…In a previous study, CKBB and respiratory chain complexes activities were both observed to be altered by monoamine-based antidepressants in rat brain (Réus et al, 2012). Moreover, overexpression of CKBB has been demonstrated to be associated with AD (Donovan et al, 2012). Our proteomic data and the results of previous studies suggest that BT may disturb energy homeostasis in the CNS of fish, potentially leading to neurodegeneration; however this hypothesis must be tested in additional experiments.…”
Section: Discussionsupporting
confidence: 46%
“…There is an increase in endocytic activities in AD brain (45), which could partially explain the uptake of mAbs by pathological neurons. Alternatively, it has been reported that AD neurons have a significantly higher amount of membrane-associated Tau protein (46). Membrane-associated pre-fibrillary Tau oligomers have been found to disrupt cell membrane integrity (47), which may allow the entry of Tau antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic analysis reported that ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCH-L1) found to be enriched in AD [50]. Amici et al [51] reported an increase of proteasome functionality in prion-associated disease and a higher incidence of protein oxidation in both aged and scrapie-infected subjects.…”
Section: Ups Functionality Increases In Prion-associated Diseasementioning
confidence: 99%